Parallele Welten. Inwiefern Literaturwissenschaft und Sprachwissenschaft voneinander profitieren können - Bock, Ursula (Glottodidactica, 2005)
The essay starts with a discussion about language as the central medium of human communication. Language is the object of research within linguistics, that analyse its structure as well as its pragmatic and communicative character. But also literature and research in literature reflect about language, its prospects and also its limits of mutual understanding. Problems of communication often arise in intercultural environments, especially under the restraints of emigration or foreign rules. Nowadays problems increase because of tendencies of globalization, that require the learning of foreign languages, but also the acquaintance with foreign cultures. Under these circumstances foreign language teaching gets more and more important to procure intercultural communicative skills. Whereas the chances of literature appear to be rather limited on this field.